Sentra Main Peran untuk Meningkatkan Kemampuan Kosakata Anak di TK Dharma Wanita Kandangan Srengat Kota Blitar - Mentari Marwa (Journal An-Nafs: Kajian Penelitian Psikologi, 2019)
Vocabulary is the basic of sentence formation, purpose of sentences will not be formed if there are no words. The richer a person's vocabulary, easier for him/her to arrange a sentence to communicate both orally and in written. This study aims to determine the effect of the application of the role playing center to increase vocabulary for children aged 4-5 years. The population and sample in this study were boys aged 4-5 years with low value criteria on the vocabulary development scale. This study used an experimental design research method. There are two groups, namely the experimental group and the control group. The analysis in this study used the Mann-Whitney U test and the Wilcoxon test.U mann-Whitney analysis obtained the average increase in scores in the experimental group (Mean Ranks on observations after treatment was 8.00and before intervention was given to 5,166) higher than the control group (Mean Ranks on observations after treatment was 3.00) This shows that the experimental group after being treated or treat in the form of a role playing center, the subject experienced an increase in vocabulary skills better than the control group where p <0.005. The Z score difference is 2,611 while the Wilcoxon p <0.005 difference Z score is 2,023. These show there are differences in vocabulary in the experimental group after being given treatment while the control group did not experience an increase where p> 0.005 and Z score 1.761